Hairy root culture of white mulberry (Morus alba L.) for a source of tyrosinase inhibitors - Hanh Thi My Nguyen; Tan Quoc Tran; Anh Lan Bui; Phuong Ngo Diem Quach (Journal of Biological Research, 2020)
White mulberry (Morus alba L.) root was reported to contain potential tyrosinase inhibitors such as norartocarpetin, streppogenin, oxyresveratrol (5, 7, 2′, 4′-tetrahydroxy-flavavone) and 2-arylbenzofuran. This study aims at investigating Morus alba L. hairy root culture to create a source of tyrosinase inhibitors for skin-whitening application. Morus alba L. leaf (including mesophyll and petiole) and stem explants were randomly wounded and inoculated with Agrobacterium rhizogenes ATCC 15834 in 10-40 minutes, and coculturing for 4 days. After inoculation, Agrobacterium rhizogenes were removed by using MS medium adding 200mg/L cefotaxime as antibiotics. Then, fresh inducted hairy roots were grown in nonphytohormone liquid medium (MS, White, Gamborg B5 or WPM) on a shaker (80rpm) at 25 ±1°C. Inducted hairy roots were tested for the present of rolB by PCR analysis and its effect on tyrosinase activity using a 96-well plate reader. The suitable explants for hairy root induction are leaves, especially petioles in 10 minutes (root induction frequency: 83%). After induction, hairy roots on MS was grown more efficiently (increased 3.933 times in FW) than on WPM, B5 and White medium. Inducted hairy roots were successfully transgenes by the present of rolB in their genome and had the same anti-tyrosinase activity as the natural roots without significance differences (IC50: 3.860 and 3.597 μg/mL, respectively). Cultured Morus alba L. hairy roots are potential source of tyrosinase inhibitors for future skin-whitening ingredient.